Multi-habitat seascape restoration: optimising marine restoration for coastal repair and social benefit - McAfee, Dominic; Reis-Santos, Patrick; Jones, Alice R.; Gillanders, Bronwyn M.; Mellin, Camille; Nagelkerken, Ivan; Nursey-Bray, Melissa J.; Baring, Ryan; da Silva, Graziela Miot; Tanner, Jason E.; Connell, Sean D. (Frontiers in Marine Science, 2022)
Marine ecosystem restoration is fast becoming the primary tool for repairing the socio-ecological functions and economic benefits of coastal seas. Healthy seascapes are characterized by many interacting species and intermingled habitats (e.g., seagrass, kelp, shellfish, sedimentary) that co-create ecological functions of substantial socio-economic value. These co-created functions not only build stability and resilience at seascape scales, but synergistically combine to enhance ecological recovery and productivity that is greater than the sum of the individual habitats. Yet, despite this knowledge, single-species approaches dominate marine restoration practice, limiting the ecological and social benefits of restoration. We propose that for ecosystem restoration to meet its potential in delivering socio-ecological benefits that are resilient to environmental change, restoration practices should plan beyond single-species of single-habitats to a multi-habitat seascape approach that not only stabilizes recovering systems but accelerates their recovery. Where multiple habitats are co-restored, their positive interactions mutually benefit each other to strengthen ecosystem recovery; such as co-restored shellfish and kelp forests on constructed reefs, which combine to stabilize sediment for seagrass recovery. As fisheries scientists and managers, food and social scientists, and ecologists and oceanographers, we describe marine restoration activities using a multi-habitat approach that is readily achievable where multiple institutions collaborate and coordinate on restoration activities.